HUBUNGAN ANTARA KEMAMPUAN KOGNITIF DAN AKTIVITAS SETIAP HARI LANJUT USIA DI PANTI JOMPO DINAS SOSIAL BINJAI - Darwita Juniwati Barus; Ida Ria Royentina Sidabukke (Jurnal Online Keperawatan Indonesia, 2023)
Impaired cognitive function in the elderly can have negative effects on the central nervous system, including decreased brain mass and reduced blood flow in the brain. This causes a decrease in interest in daily activities for the elderly. At the Binjai Social Service Nursing Home, many elderly people need assistance in carrying out their routines which previously could be done alone. Research was conducted to determine the relationship between cognitive abilities and daily activities in the elderly at the Binjai Social Service Nursing Home. The research method used is descriptive correlation with a cross-sectional approach. The population of this study were all elderly people at the UPT Social Service for the Elderly of the Binjai Social Service who were ≥ 60 years old, with a total of 160 people, and a sample of 114 people was taken using the Consecutive Sampling technique. Data were analyzed using the Spearman rho test. Research shows that the majority of the elderly experience probable cognitive impairment (50.0%) and the majority also experience a moderate level of dependence in carrying out daily activities (71.1%). With the Spearman rho test, it was found that there was a significant relationship between cognitive function and daily activities (p value = 0.000). Based on these findings, researchers recommend that the elderly improve their cognitive function in order to improve their ability to carry out daily activities. Thus, the elderly can remain independent and active in carrying out their routines every day.